Analisis Kemampuan Berpikir Kreatif Matematis Siswa SMP pada Materi Bangun Ruang - Nuramadina, Agilia; Damanik, Anggi Nur Rahayu; Triono, Didik Wahyu; Hati, Lara; Putri, Natasya Meisandi; Gusnaida, Riva; Yolanda, Fitriana (Universitas Nusantara PGRI Kediri, 2023)
Mathematics is an important subject in basic education, including in junior high schools, which plays a role in developing students' logical, critical, systematic, and creative thinking skills. The material on spatial figures related to the concept of three-dimensional space is often a challenge because it requires visualization and in-depth understanding. This study aims to analyze the mathematical creative thinking skills of junior high school students on spatial figures and the factors that influence them. The method used is qualitative with a literature study approach. The results of the study show that students' creative thinking skills are still low, caused by monotonous learning and inadequate methods. Several creative strategies for teaching spatial figures, such as the use of physical models, technology and educational games, are proposed to improve students' mathematical creative thinking skills. These findings are expected to help mathematics teachers develop more effective learning strategies.